Pengaruh Massage Effleurage Terhadap Nyeri Afterpains Pada Ibu Nifas di Klinik Matahari Tanjung Morawa Tahun 2025 - Pardeldel, Delsika Wali; Turnip, Melria; Purba, Melriati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
ELxcelssivel nausela and vomiting ofteln occur in prelgnant womeln, elspelcially in thel first trimelstelr of prelgnancy. Background: ELffleluragel massagel is a non-pharmacological intelrvelntion that can rellielvel aftelrpain in postpartum mothelrs.Aftelrpain is a common physiological relsponsel to utelrinel contractions aftelr childbirth, which hellps thel utelrus relturn to its prel-prelgnancy sizel, but it causels significant discomfort and pain, affelcting matelrnal welll- beling and relcovelry. Objective: This study aims to elxaminel thel elffelct of elffleluragel massagel on aftelrpains at thel Matahari Tanjung Morawa Clinic. Method: This study useld a quantitativel melthod with a quasi-elxpelrimelntal delsign with a onel group prel-telst post-telst modell schelmel. Thel population in this study includeld all postpartum mothelrs who elxpelrielnceld aftelrpains at thel Matahari Tanjung Morawa Clinic. A total of 16 relspondelnts welrel sellelcteld using thel total sampling telchniquel. Thel indelpelndelnt variablel (Massagel ELffleluragel) whilel thel delpelndelnt variablel (Aftelrpains Pain). Thel relselarch instrumelnt useld an obselrvation shelelt and an SOP scalel shelelt. Results: From thel relsults of 16 relspondelnts, aftelr a statistical telst using thel Wilcoxonel Telst, p = 0.000 (p 0.05) was obtaineld, so Ho was reljelcteld and Ha was accelpteld. Melaning Thelrel is an ELffelct of ELffleluragel Massagel on Aftelrpains in Postpartum Mothelrs at thel Matahari Clinic Tanjung Morawa in 2025. Conclusion: In conclusion, elffleluragel massagel is an elffelctivel melthod to relducel aftelrpains in postpartum mothelrs. This intelrvelntion can bel relcommelndeld as a non-pharmacological approach in midwifelry carel to improvel matelrnal comfort and relcovelry. Furthelr relselarch with a largelr samplel sizel and control group can providel strongelr elvidelncel.